Swarm Robot Implementation in Gas Searching Using Particle Swarm Optimization Algorithm - Nyayu Latifah Husni; Ade Silvia; Siti Nurmaini; Falah Yuridho; Irsyadi Yani (Universitas Sriwijaya, 2017)
In this reseach, a PSO method is impelemented in searching a gas leakage. A swarm robot consisted of 3 agents, yelow, blue, and green, was used. The research was done in 2 type of experiments, i.e. in simulation and real expeiment. A Matlab is used as a simulation validation while for the real experiment, a 2 x 2 m arena is used. From the experiment, it can be concluded that a good performance of a swam can be achieved using PSO method.